Interferon activation in bone marrow long-lived plasma cells in systemic lupus erythematosus - Alzamareh, Diana F.; Meednu, Nida; Nandedkar-Kulkarni, Neha; Krenitsky, Daria; Barnard, Jennifer; Yasaka, Ken; Durrett, Wesley; Thakar, Juilee; Rangel-Moreno, Javier; Anolik, Jennifer H.; Barnas, Jennifer L. (Frontiers in Immunology, 2025)
While durable antibody responses from long-lived plasma cell (LLPC) populations are important for protection against pathogens, LLPC may be harmful if they produce antibodies against self-proteins or self-nuclear antigens as occurs in autoimmune diseases such as systemic lupus erythematosus (SLE). Thus, the elimination of autoreactive LLPC may improve the treatment of antibody-driven autoimmune diseases. However, LLPC remain a challenging therapeutic target. Here, we compare the matched bone marrow (BM) and peripheral blood (PBL) plasma cell (PC) compartments of SLE and healthy donors (HD). We show a similar distribution of CD138- and CD138+ PC, including putative LLPC (CD19- CD138+ CD38+), between SLE and HD BM. For both SLE and HD, CD138+ PC are at a higher frequency in BM than PBL. Expression of Ki-67 associates with the PBL compartment where it is found on all PC subsets regardless of CD19 or CD138 expression. Transcriptomic analysis identifies an interferon (IFN) gene signature in transitional B cells in the SLE BM, but surprisingly also in the BM PC derived from SLE. BM PC and B cells phosphorylate STAT1 in response to type I IFN stimulation in vitro, but with decreased fold change compared to those from the PBL. While BM PC bind type I IFN receptor-blocking antibody anifrolumab, it is to a lesser degree than circulating B cells. Anti-nuclear autoantibodies (ANA) are found in the BM supernatant and PBL serum of SLE patients. Both SLE and HD BM-derived PC have increased survival compared to their PBL counterparts when treated with verdinexor. In summary, these findings show evidence of IFN activation in BM PC from SLE.